The effect of swedish massage using ginger oil on chronic low back pain - Bahri, Syuhada; Nugroho, Sigit; Sumaryanti, Sumaryanti; Mulyawan , Rizki; Ginanjar, Agi; Pongsiri, Tatpicha; Panganiban, Teejay D. (Universitas Negeri Malang, 2024)
Background: Chronic low back pain is one of the musculoskeletal health problems that is common in society, including athletes. Chronic low back pain occurs in people in various countries, including Indonesia, with estimates that they experience pain that lasts approximately 24 hours for 3 months or more and often occurs at the age of 20-40 years. Disorders found in chronic low back pain sufferers usually experience pain in the lower back area. By using Swedish massage, which is a massage method to relax muscles, reduce pain and improve blood circulation, plus the use of ginger oil, which is a formulation commonly used to relieve pain and also as aromatherapy, can reduce the problem of chronic lower back pain. Objective: The aim of this study was to test the effect of Swedish massage using ginger oil on chronic low back pain. Methods: The research method uses experiments with a one-group pretest-posttest design. There were 7 participants taken using incidental sampling. The research instrument used the Visual Analogue Scale. The data analysis technique uses descriptive statistics and paired samples t test. Results: The research results obtained tcount = 6.33 with Sig. 0.00 < 0.05 which means there is an influence of SM using ginger oil on CLBP. Conclusion: This research concluded that there was an effect of Swedish massage using ginger oil on chronic low back pain. Further research with more participants is needed. Thus, the research results can be generalized, especially to women who have not been able to reveal anything in this research.